Pengaruh pendidikan Kewirausahaan, Digital Literacy dan Self Efficacy Terhadap Minat Berwirausaha Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang - Putri, Wardana; Nurhajati, Nurhajati; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to determine the influence of entrepreneurship education, digital literacy and self-efficacy on increasing interest in entrepreneurship. The object of this research is students from the Faculty of Economics and Business, Islamic University of Malang with a sample size of 82 students with the record that they have taken entrepreneurship courses and do not yet have a business. The sampling technique used was purposive sampling. Data collection techniques use questionnaires and data analysis tools. This research uses a quantitative approach because the data is obtained in the form of numbers. Based on the results of research analysis, entrepreneurship education has a positive and significant effect on interest in entrepreneurship. digital literacy has a positive and significant effect on interest in entrepreneurship. and self-efficacy has a positive and significant effect on interest in entrepreneurship. Keywords: Entrepreneurship education, digital literacy, self-efficacy and interest in entrepreneurship